LARANGAN PERKAWINAN BEDA AGAMA MENURUT MAHKAMAH AGUNG DALAM SEMA NOMOR 2 TAHUN 2023 - Pitaloka, Diah Marla; Djaja, Benny; Sudirman, Maman (Fakultas Hukum Universitas Ngurah Rai, 2024)
Interfaith marriages are not something new for multicultural Indonesian society. Interfaith marriages are common in society and have been going on for a long time. However, this does not mean that interfaith marriages are not problematic by society. In fact, the Marriage Law in Article 2 paragraph (1) determines that marriage is valid if it is carried out according to the laws of each religion and belief. From the Indonesian Conference on Religion and Peace, it was recorded that 1,425 couples of different religions were married in Indonesia in the period from 2005 to early March 2022, this made the Supreme Court finally issue a decree prohibiting interfaith marriages with Circular Letter (SEMA) Number 2 of 2023. The purpose of this writing is to 1) analyze the legality of interfaith marriages according to positive law in Indonesia and 2) analyze the effectiveness of the Supreme Court's decision in SEMA Number 2 of 2023. The conclusion obtained from this writing is that even though Article 8 of Law Number 12 of 2011 concerning the Establishment of Legislative Regulations states that the existence of regulations stipulated by the Supreme Court (SEMA) is recognized and has binding legal force, however, many people think that SEMA is in conflict with the Population Administration Law which does not prohibit the registration of interfaith marriages. SEMA Number 2 of 2023 does not necessarily eliminate interfaith marriages, because if we review their effectiveness, this will return to the awareness of each community.